The Essence of Enterprise Communications and Their Role in the Process of Enterprise Management - Voit Bohdan R. (Bìznes Inform, 2023)
The purpose of the article is to analyze, along with further improvement and adaptation, the essence and importance of communications to the management system of enterprises and organizations in the current conditions of their functioning. The article analyzes and shows the role of communications in the functioning of enterprises depending on a particular type of enterprise activity. The analysis of existing studies allowed to identify the approaches from which scholars consider the concept of communication, namely: philosophical, social, linguistic, economic, and psychological. Among the most relevant definitions of «communication» for today’s events in Ukraine, the study chose the most appropriate interpretation of the concept of communication as a process by which we provide and transmit meaning in an attempt to create a common understanding. This process requires a huge set of skills. This interpretation helps to adapt the definition as accurately as possible to the events currently taking place in our country and in business, when it is necessary to reflect a common understanding of the situation. Also, based on the analysis of current definitions of the concept of «communication», the author has proposed his own vision of this concept and defined communication as an opportunity to unite like-minded people whose goal is to solve a certain problem with the possible further maintenance of relations to maintain a common understanding of a situation or event. In general, the results of the analysis show that the understanding of the content of communication in the management system of enterprises and organizations has certain peculiarities depending on their activities and the approach used for analysis. Managers at enterprises should take a more balanced approach to understanding the communication process, as this will ensure the formation of an internal microclimate in the team, successful interaction both within the organization and externally, and, ultimately, will help to increase the efficiency of the management process.